The Effect of Teacher Personality Competence on Accounting Learning Motivation in XII IIS Class Students of SMA Negeri 2 Barru - Ira Ayu Puspitasari; Nuraisyiah Nuraisyiah; Muhammad Azis; M. Ridwan Tikollah; Sahade Sahade (UNIVED Press, 2024)
This study aims to determine the effect of the teacher's personality competence on motivation to learn accounting in class XII IIS SMA Negeri 2 Barru. The population of this study was all students of class XII IIS SMA Negeri 2 Barru, totaling 85 students, while the sample used a saturated sampling technique with a total sample as many as 85 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive statistical analysis, instrument testing and hypothetical testing using SPSS 25 for windows. The results showed that: 1) Based on the results of descriptive statistical analysis, teacher personality competence was 74.88 percent in the good category and learning motivation was 81.22 in the very good category. (2) Based on the results of a simple linear analysis, it was obtained that teacher's personality competency Y = 46.150 + 0.328X, which means that for each addition of one teacher's personality competency value, the value of learning motivation increases by 0.328. 3) From the results of the t-test analysis, the significance value is 0.001 <0.05, which means that the teacher's personality competency variable has a positive and significant effect on motivation to learn accounting in class XII IIS students at SMA Negeri 2 Barru, thus the hypothesis is